Corpus Callosum Diffusion and Connectivity Features in High Functioning Subjects With Pyridoxine-Dependent Epilepsy. - Poliachik, Sandra L.; Friedman, Seth D.; Poliakov, Andrew V.; Budech, Christopher B.; Ishak, Gisele E.; Shaw, Dennis W.W.; Jr.,Gospe, Sidney M.; Gospe, Sidney M Jr (Pediatric Neurology, 2016)
Background: In this observational study, white matter structure, functional magnetic resonance imaging (fMRI) task-based responses, and functional connectivity were assessed in four subjects with high functioning pyridoxine-dependent epilepsy and age-matched control subjects.Methods: Four male subjects with pyridoxine-dependent epilepsy (mean age 31 years 8 months, standard deviation 12 years 3 months) and age-matched control subjects (32 years 4 months, standard deviation 13 years) were recruited to participate in the study. Diffusion tensor data were collected and postprocessed in Functional Magnetic Resonance Imaging of the Brain Software Library to quantify corpus callosum tracts as a means to assess white matter structure. Task-based fMRI data were collected and Functional Magnetic Resonance Imaging of the Brain Software Library used to assess task response. The fMRI resting-state data were analyzed with the functional connectivity toolbox Conn to determine functional connectivity.Results: Subjects with high functioning pyridoxine-dependent epilepsy retained structural white matter connectivity compared with control subjects, despite morphologic differences in the posterior corpus callosum. fMRI task-based results did not differ between subjects with pyridoxine-dependent epilepsy and control subjects; functional connectivity as measured with resting-state fMRI was lower in subjects with pyridoxine-dependent epilepsy for several systems (memory, somatosensory, auditory).Conclusion: Although corpus callosum morphology is diminished in the posterior portions, structural connectivity was retained in subjects with pyridoxine-dependent epilepsy, while functional connectivity was diminished for memory, somatosensory, and auditory systems.